PENGARUH KUALITAS SISTEM, KUALITAS INFORMASI, KUALITAS LAYANAN DAN KUALITAS PELATIHAN TERHADAP KINERJA INDIVIDUAL PADA BANK PEREKNOMIAN RAKYAT (BPR) - Prasetyo, Bagas Haris; Ariyanto, Dodik (E-Jurnal Ekonomi dan Bisnis Universitas Udayana; VOLUME.14.NO.02.TAHUN.2025, 2025)
This study aims to examine the influence of system quality, information quality, service quality, and training quality on individual performance at the People’s Economy Bank (BPR) by applying the DeLone & McLean success model. The research was conducted across all BPR branches in Denpasar city, and the data used was derived from respondents' answers to the questionnaire statements. The sampling method employed in this study was purposive sampling, with a sample size of 85 respondents who use the accounting information system at BPR Denpasar. Data analysis was conducted using multiple linear regression. The findings indicate that information quality and service quality have a positive and significant effect on individual performance, while system quality and training quality have a negative and insignificant effect on individual performance. These findings can serve as a consideration for the People’s Economy Bank (BPR) to enhance system quality, information quality, service quality, and training quality to improve individual performance at BPR.